Are Migraine With and Without Aura Really Different Entities? - Kincses, Zsigmond Tamás; Veréb, Dániel; Faragó, Péter; Tóth, Eszter; Kocsis, Krisztián; Kincses, Bálint; Király, András; Bozsik, Bence; Párdutz, Árpád; Szok, Délia; Tajti, János; Vécsei, László; et al. (Frontiers in Neurology, 2019)
Background: Migraine research is booming with the rapidly developing neuroimaging tools. Structural and functional alterations of the migrainous brain were detected with MRI. The outcome of a research study largely depends on the working hypothesis, on the chosen measurement approach and also on the subject selection. Against all evidence from the literature that migraine subtypes are different, most of the studies handle migraine with and without aura as one disease. Methods: Publications from PubMed database were searched for terms of “migraine with aura,” “migraine without aura,” “interictal,” “MRI,” “diffusion weighted MRI,” “functional MRI,” “compared to,” “atrophy” alone and in combination. Conclusion: Only a few imaging studies compared the two subforms of the disease, migraine with aura, and without aura, directly. Functional imaging investigations largely agree that there is an increased activity/activation of the brain in migraine with aura as compared to migraine without aura. We propose that this might be the signature of cortical hyperexcitability. However, structural investigations are not equivocal. We propose that variable contribution of parallel, competing mechanisms of maladaptive plasticity and neurodegeneration might be the reason behind the variable results.